2016
DOI: 10.1590/s1677-5538.ibju.2015.0225
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar transurethral enucleation and resection of the prostate versus bipolar resection of the prostate for prostates larger than 60gr: A retrospective study at a single academic tertiary care center

Abstract: Objective:To evaluate the efficacy and safety of bipolar transurethral enucleation and resection of the prostate (B-TUERP) versus bipolar transurethral resection of the prostate (B-TURP) in the treatment of prostates larger than 60g.Material and Methods:Clinical data for 270 BPH patients who underwent B-TUERP and 204 patients who underwent B-TURP for BPH from May 2007 to May 2013 at our center were retrospectively analyzed. Outcome measures included operative time, decreased hemoglobin level, total prostate sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 22 publications
3
18
0
1
Order By: Relevance
“…Ahmad et al reported that the duration of the resection and operating time was shorter in M-TURP than B-TURP and suggested urologists save time by using M-TURP [7]. Transurethral plasmakinetic enucleation and resection of the prostate (TUERP) is superior to B-TURP in the management of large volume BPH in terms of efficacy and safety, but needs to be validated in further prospective, randomized, controlled studies [18]. A steep operative learning curve may be the main obstacle to the widespread use of TUERP [19].…”
Section: Discussionmentioning
confidence: 99%
“…Ahmad et al reported that the duration of the resection and operating time was shorter in M-TURP than B-TURP and suggested urologists save time by using M-TURP [7]. Transurethral plasmakinetic enucleation and resection of the prostate (TUERP) is superior to B-TURP in the management of large volume BPH in terms of efficacy and safety, but needs to be validated in further prospective, randomized, controlled studies [18]. A steep operative learning curve may be the main obstacle to the widespread use of TUERP [19].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, almost all patients experience gradual improvement over a period of 3-6 months [32,33]. Moreover, looking at the rate of urethral stricture and bladder neck contracture, no difference has been noticed between TUERP and TURP [27].…”
Section: Complicationsmentioning
confidence: 98%
“…Although functional outcomes were comparable, the significant difference in the amount of removed tissue and postoperative PSA and PVR may support a more durable symptom relieve in favor of TUERP. Another retrospective study assessed the outcome of bipolar TUERP versus bipolar TURP for prostates larger than 60 ml [27]. In that study TUERP had a better outcome in terms of operative time, irrigation time and hospital stay.…”
Section: Clinical Outcomesmentioning
confidence: 99%
See 2 more Smart Citations